2020
DOI: 10.1001/jamaoncol.2019.6400
|View full text |Cite
|
Sign up to set email alerts
|

Association of Germline Genetic Testing Results With Locoregional and Systemic Therapy in Patients With Breast Cancer

Abstract: IMPORTANCEThe increasing use of germline genetic testing may have unintended consequences on treatment. Little is known about how women with pathogenic variants in cancer susceptibility genes are treated for breast cancer.OBJECTIVE To determine the association of germline genetic testing results with locoregional and systemic therapy use in women diagnosed with breast cancer.DESIGN, SETTING, AND PARTICIPANTS For this population-based cohort study, data from women aged 20 years or older who were diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 50 publications
(77 reference statements)
2
40
1
Order By: Relevance
“…Therefore, the exact reasons for the uptake of these procedures have not been elucidated. These findings indicate the overuse of prophylactic mastectomy, based on the calculated cumulative breast cancer risks for females with CHEK2 pathogenic variants, in line with other studies [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the exact reasons for the uptake of these procedures have not been elucidated. These findings indicate the overuse of prophylactic mastectomy, based on the calculated cumulative breast cancer risks for females with CHEK2 pathogenic variants, in line with other studies [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…These studies include data to suggest high rates of bilateral mastectomy reported among breast cancer patients with a BRCA1/2 variant of uncertain significance [33], as well as those with non-BRCA1/2 moderate penetrance genes [34,35], suggesting potential overtreatment. Additionally, a recently published cancer registry-based study suggested that those with P/LP BRCA1/2 and other breast cancer-associated genes may have patterns of breast cancer treatment which are less concordant with practice guidelines; including being more likely to receive bilateral mastectomy for a unilateral tumor, less likely to receive post-lumpectomy radiotherapy, and more likely to receive chemotherapy for early-stage, ER/PR-positive disease [34]. Similarly, studies from us and others have reported on risk-reducing oophorectomies conducted among those with BRCA1/2 carriers have reported lower rates among Black women compared to non-Hispanic whites [36].…”
Section: Updated Guidelines To Address Low Genetic Testing Ratesmentioning
confidence: 99%
“…Using inherited breast cancer as an example, follow-up strategies to manage elevated breast cancer risks may include either enhanced breast cancer screening or bilateral mastectomy for high penetrance genes, such as BRCA1/2 and PALB2 [28]. In contrast, only heightened screening is recommended for those with P/ LP variants in moderate penetrance genes, such as ATM and CHEK2; yet, prior research by us and others suggests that some women have bilateral mastectomies even though it may not be medically justified [29,30]. Furthermore, while risk-reducing oophorectomy is recommended for BRCA1/2 carriers around the age of 35-45, there is insufficient evidence to recommend this procedure for all women with ATM, CHEK2, or PALB2 P/LP variants [28]; however, our prior study suggested that some of these women still have oophorectomies [29].…”
Section: Introductionmentioning
confidence: 99%